Variability in clinicians' opinions regarding fitness to drive in patients with obstructive sleep apnoea syndrome (OSAS). Issue 5 (19th November 2014) - Dwarakanath, A; Twiddy, M; Ghosh, D; Jamson, S L; Baxter, P D; Elliott, M W; ,
Abstract : We evaluated clinicians' current practice for giving advice to patients with obstructive sleep apnoea syndrome. Clinicians were invited to complete a web-based survey and indicate the advice they would give to patients in a number of scenarios about driving; they were also asked what they considered to be residual drowsiness and adequate compliance following CPAP treatment. In the least contentious scenario, 94% of clinicians would allow driving; in the most contentious a patient had a 50% chance of being allowed to drive. Following treatment with CPAP, clinicians' interpretation of what constituted residual drowsiness was inconsistent. In each vignette the same clinician was more likely to say 'yes' to 'excessive' than to 'irresistible' (71%±12% vs 42%±10%, p=0.0045). There was also a lack of consensus regarding 'adequate CPAP compliance'; 'yes' responses ranged from 13% to 64%. There is a need for clearer guidance; a recent update to the Driver and Vehicle Licensing Agency guidance, and a statement from the British Thoracic Society, making it clear that sleepiness while driving is the key issue, may help.